Composite body movements modulate numerical cognition: evidence from the motion-numerical compatibility effect - Cheng, Xiaorong; Ge, Hui; Andoni, Deljfina; Ding, Xianfeng; Fan, Zhao (Frontiers in Psychology, 2015)
A recent hierarchical model of numerical processing, initiated by Fischer and Brugger (2011) and Fisher (2012), suggested that situated factors, such as different body postures and body movements, can influence the magnitude representation and bias numerical processing. Indeed, Loetscher and colleagues (2008) found that participants’ behavior in a random number generation (RNG) task was biased by head rotations. More small numbers were reported after leftward than rightward head turns, i.e. a motion–numerical compatibility effect. Here, by carrying out two experiments, we explored whether similar motion–numerical compatibility effects exist for movements of other important body components, e.g. arms, and for composite body movements as well, which are basis for complex human activities in many ecologically meaningful situations. In Experiment 1, a motion-numerical compatibility effect was observed for lateral rotations of two body components, i.e., the head and arms. Relatively large numbers were reported after making rightward compared to leftward movements for both lateral head and arm turns. The motion-numerical compatibility effect was observed again in Experiment 2 when participants were asked to perform composite body movements of congruent movement directions, e.g., simultaneous head left turns and arm left turns. However, it disappeared when the movement directions were incongruent, e.g., simultaneous head left turns and arm right turns. Taken together, our results extended Loetscher et al.'s (2008) finding by demonstrating that their effect is effector-general and exists for arm movements. Moreover, our study reveals for the first time that the impact of spatial information on numerical processing induced by each of the two sensorimotor-based situated factors, e.g., a lateral head turn and a lateral arm turn, can cancel each other out.